Highly divergent 18S rRNA gene paralogs in a Cryptosporidium genotype from eastern chipmunks (Tamias striatus) - Stenger, Brianna L S; Clark, Mark E; Kváč, Martin; Khan, Eakalak; Giddings, Catherine W; Dyer, Neil W; Schultz, Jessie L; McEvoy, John M (Infection, genetics and evolution, 2015)
Cryptosporidium is an apicomplexan parasite that causes the disease cryptosporidiosis in humans, livestock, and other vertebrates. Much of the knowledge on Cryptosporidium diversity is derived from 18S rRNA gene (18S rDNA) phylogenies. Eukaryote genomes generally have multiple 18S rDNA copies that evolve in concert, which is necessary for the accurate inference of phylogenetic relationships. However, 18S rDNA copies in some genomes evolve by a birth-and-death process that can result in sequence divergence among copies. Most notably, divergent 18S rDNA paralogs in the apicomplexan Plasmodium share only 89-95% sequence similarity, encode structurally distinct rRNA molecules, and are expressed at different life cycle stages. In the present study, Cryptosporidium 18S rDNA was amplified from 28/72 (38.9%) eastern chipmunks (Tamias striatus). Phylogenetic analyses showed the co-occurrence of two 18S rDNA types, Type A and Type B, in 26 chipmunks, and Type B clustered with a sequence previously identified as Cryptosporidium chipmunk genotype II. Types A and B had a sister group relationship but shared less than 93% sequence similarity. In contrast, actin and heat shock protein 70 gene sequences were homogeneous in samples with both Types A and B present. It was therefore concluded that Types A and B are divergent 18S rDNA paralogs in Cryptosporidium chipmunk genotype II. Substitution patterns in Types A and B were consistent with functionally constrained evolution; however, Type B evolved more rapidly than Type A and had a higher G+C content (46.3% versus 41.0%). Oocysts of Cryptosporidium chipmunk genotype II measured 4.17 μm (3.73-5.04 μm) × 3.94 μm (3.50-4.98 μm) with a length-to-width ratio of 1.06 ± 0.06 μm, and infection occurred naturally in the jejunum, cecum, and colon of eastern chipmunks. The findings of this study have implications for the use of 18S rDNA sequences to infer phylogenetic relationships.
Keywords: Molecular Sequence Data; Prevalence; Actins; genotyp; Cryptosporidium; Cryptosporidiosis; Genotype; 18S rDNA; HSP70 Heat-Shock Proteins; prevalence; aktiny; RNA ribozomální 18S; sekvence nukleotidů; Base Sequence; 18S rRNA; Paralogy; zvířata; fylogeneze; RNA, Ribosomal, 18S; Sciuridae; molekulární sekvence - údaje; kryptosporidióza; proteiny tepelného šoku HSP70; Phylogeny; Animals